Association of SIGLEC9 Expression with Cytokine Expression, Tumor Grading, KRAS, NRAS, BRAF, PIK3CA, AKT Gene Mutations, and MSI Status in Colorectal Cancer - Błażej Ochman; Anna Kot; Sylwia Mielcarska; Agnieszka Kula; Miriam Dawidowicz; Dominika Koszewska; Dorota Hudy; Monika Szrot; Jerzy Piecuch; Dariusz Waniczek; Zenon Czuba; Elżbieta Świętochowska (Current Issues in Molecular Biology)
SIGLEC9 (sialic acid-binding Ig-like lectin 9) is a molecule thought to have a significant influence on the immune properties of the colorectal cancer (CRC) tumor microenvironment (TME). In our study, we assessed the expression of the SIGLEC9 protein in CRC tissue and the surgical margin tissue. Using RT-PCR, we analyzed mutations in the KRAS, NRAS, BRAF, PIK3CA, and AKT genes. We observed a significantly elevated expression of the SIGLEC9 protein in CRC tissue compared to the control group. No significant differences were observed in SIGLEC9 protein expression depending on mutations in the KRAS, NRAS, BRAF, PIK3CA, and AKT genes or microsatellite instability (MSI) status. However, we found a significantly higher expression of the SIGLEC9 protein in high-grade tumors compared to the low-grade tumors group. SIGLEC9 expression was significantly associated with the expression of multiple cytokines, chemokines, and growth factors in the CRC TME. These associations suggest the significant potential of SIGLEC9 as a molecule that plays a crucial role in shaping the immune properties of the CRC TME, as well as its potential therapeutic relevance, particularly in the group of high-grade CRC tumors.